2017
DOI: 10.1042/etls20170085
|View full text |Cite
|
Sign up to set email alerts
|

Use of CRISPR systems in plant genome editing: toward new opportunities in agriculture

Abstract: Initially discovered in bacteria and archaea, CRISPR-Cas9 is an adaptive immune system found in prokaryotes. In 2012, scientists found a way to use it as a genome editing tool. In 2013, its application in plants was successfully achieved. This breakthrough has opened up many new opportunities for researchers, including the opportunity to gain a better understanding of plant biological systems more quickly. The present study reviews agricultural applications related to the use of CRISPR systems in plants from 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
78
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 196 publications
(87 citation statements)
references
References 64 publications
0
78
0
1
Order By: Relevance
“…The same cautious optimism seems to prevail also among some other EU countries. Ricroch et al (2017) listed 52 peer-reviewed articles published in 2014-2017, all applying CRISPR systems in plants within an agricultural context. They found that EU (9 studies, carried out in Austria, Belgium, France, Germany, Hungary, Sweden and the United Kingdom) is, together with China (22 studies) and United States (10 studies) among the regions in the world with most published proof-of-concept studies for CRISPR applications within this context.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The same cautious optimism seems to prevail also among some other EU countries. Ricroch et al (2017) listed 52 peer-reviewed articles published in 2014-2017, all applying CRISPR systems in plants within an agricultural context. They found that EU (9 studies, carried out in Austria, Belgium, France, Germany, Hungary, Sweden and the United Kingdom) is, together with China (22 studies) and United States (10 studies) among the regions in the world with most published proof-of-concept studies for CRISPR applications within this context.…”
Section: Discussionmentioning
confidence: 99%
“…The most widely known so far is the clustered regularly interspaced short palindromic repeats (CRISPR) system, including a CRISPR associated (Cas) endonuclease protein, while zinc finger nucleases, transcription activator‐like effector nucleases (TALENs) and the nucleic acid‐based oligonucleotide‐directed mutagenesis (ODM) are also routinely applied. It is beyond the scope of this review to describe the genome editing techniques in detail; however, several recent reviews are available on various aspects, such as the technical details (NTWG , Chen and Gao , Abdallah et al , Hilscher et al , HLG SAM , entire issue of Plant Biotechnology Journal ), specifically on CRISPR systems (Bortesi and Fischer , Ding et al , Paul III and Qi , Samanta et al , Stella and Montoya , Arora and Narula , Volpi e Silva and Patron , Yin et al ), applications in plants (Brinegar et al , Hilscher et al , Ricroch et al , Zhang et al ), as well as the historical development (Songstad et al ) and comparisons with other breeding techniques (Georges and Ray ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Parasitic weed resistance based on the editing of specific target genes using CRISPR/Cas9, can be easily applied to other susceptible crops and this method could be effective with other host plant, to develop parasite resistance. In addition, the host plants are not considered genetically modified organisms due to lack of any foreign DNA sequences in the mutated host plants 49 . One of the major challenges associated with CRISPR/Cas9 system is off-target cleavage due to non-specificity of the selected sgRNA with other few base pair mismatched target site within the genome 50 .…”
Section: Discussionmentioning
confidence: 99%
“…Components of bacterial CRISPR (Clustered Regulatory Interspaced Short Palindromic Repeats) systems for adaptive immunity have been repurposed for engineering the genomes of eukaryotic organisms (1)(2)(3). These molecular tools have been rapidly and successfully applied in many organisms, including plants (for recent reviews see Gao, 2018;Ricroch et al, 2017;Yin et al, 2017), primarily due to the ease at which they can be programmed to recognise new genomic targets. The majority of plant genome engineering studies have utilised Cas9 (CRISPR Associated Protein 9) from Streptococcus pyogenes, a monomeric nuclease found in the Type II CRISPR system of that species.…”
Section: Introductionmentioning
confidence: 99%